PAX8 EXPRESSION AND ITS ASSOCIATIONS IN PRIMARY RENAL CELL CARCINOMA: A CROSS SECTIONAL STUDY - Zamir, Ahmed; Akhtar, Farhan; Waqar, Samina; Hanif, Aminah (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the frequency of PAX8 expression in cases of primary renal cell carcinoma (RCC) and its association with patient demographics and tumor type.Study Design: Cross sectional study.Place and Duration of Study: Department of Histopathology, Armed Forces Institute of Pathology, Rawalpindi, from Jun 2016 to Jun 2017.Methodology: After ethics approval, 57 cases were selected by non probability consecutive sampling. Inclusion criteria was diagnosis of primary renal cell carcinoma of all histological types, in both genders, among adults aged >18 years. Exclusion criteria were poorly fixed specimens and metastatic renal cell carcinoma. The main outcome measure was PAX8 frequency in renal cell carcinoma. The secondary outcome measure was correlation of PAX8 expression with age, gender, tumor type and grade. Data was entered and analyzed on Statistical Package for the Social Sciences.Results: Out of 57 cases, majority were males 37, (64.9%). The mean age was 55.35 ± 12.60 years. Clear cell carcinoma was the most frequent histopathologic variant in 47 (81%) cases followed by papillary carcinoma in 6 (10.2%), chromophobe cell carcinoma 2 (3.5%), sarcomatoid renal carcinoma 1 (1.75%) and mucinous tubular and spindle cell carcinoma 1 (1.75%). PAX8 expression was positive in 52 (91.2%). No significant difference was found in the frequency of PAX8 expression across age (p=0.321), gender (p=1.00) and tumor type (p=1.00). There was significant difference seen across tumor grade p=0.03.Conclusion: PAX8 is an important additional diagnostic marker for renal cell carcinoma. It can be recommended for inclusion in immunohistochemical panel for diagnosis..............